(untitled) (Research in Agriculture Livestock and Fisheries, 2023)
The present study was conducted to evaluate the effect of traditional Bengal culinary practice on the heavy metal content of four carp species (Labeo rohita, Catla catla, Cirrhinus cirrhosus, and Hypophthalmichthys molitrix). Fish samples were collected from seven different farms located in the Rajshahi district of Bangladesh. The collected samples were processed and cooked in a traditional currying method and concentrations of five heavy metals (Pb, Co, Cr, Cd, and Ni) were assessed in raw and cooked fish using a flame atomic spectrophotometer. Heavy metal concentrations were significantly reduced in the cooked samples with a few exceptions. The metal pollution index (MPI) indicated that the most amount of heavy metals was lost in C. cirrhosus followed by H. molitrix, L rohita, and C. catla. Pb was the most abundant and consumed of the tested heavy metals in the cooked fish followed by Co, Ni, Cd, and Cr respectively. Health risk index (HRI) and target hazard quotient (THQ) revealed that individual heavy metal intake from cooked fish does not pose any threat to human health. However, the hazard index (HI) of the accumulated heavy metals in the cooked fish suggested that the long-term effect of consuming heavy metal contaminated fish could collectively lead to possible non-carcinogenic health complexities. Additionally, HI also implied that the highest degree of health risk is associated with the consumption of H. molitrix and the least with L. rohita. Vol. 9, No. 3, December 2022: 367-376